Stages of behavior change for physical activity in adolescents from the amazon Estágios de mudança de comportamento para a atividade física em adolescentes da região amazônica - Pinto A.A.* (2017)
© 2017, Universidade Federal de Santa Catarina. All rights reserved.The aim of this study was to estimate the prevalence of stages of behavior change (SBC) for physical activity and to verify the associated demographic and economic factors, in adolescents from the Amazon. A total of 2.517 adolescents (aged 14-19 years) from public high schools participated of the study. SBC for physical activity, demographic (sex, age, school year, school shift and residence area) and economic factors (occupational status, family income and maternal schooling) were investigated. The associations between SBC and independent variables were tested by multinomial logistic regression. Most adolescents were in the maintenance stage (40.8%) and the minority was in pre-contemplation stage (9.0%). Female adolescents were more likely of being in the action (OR=1.44; CI95%=1.14-1.81), preparation (OR=2.71; CI95%=2.14-3.44), contemplation (OR=2.89; CI95%=2.25-3.69) and pre-contemplation (OR=2.91;CI 95%=2.16-4.00) stages compared to male adolescents. Adolescents aged 16-17 years were less likely of being in the action stage (OR=0.71; CI95%=0.53-0.94) and those aged 18-19 years were more likely of being in the preparation stage (OR=1.50; CI95%=1.04-2.16) compared to those aged 14-15 years. Family income of six minimum wages or more was associated to higher chances of being in the action (OR=2.09; CI95%=1.38-3.17), preparation (OR=2.02; CI95%=1.31- 3.12) and contemplation (OR=1.87; IC95%=1.18-2.95) stages. Adolescents who worked were less likely of being in the pre-contemplation stage (OR=0.45; CI95%=0.27-0.74), compared to those who do not work. Most of adolescents were in the maintenance stage for physical activity. The factors associated to SBC were female sex, age groups of 16-17 years and 18-19 years, income of six minimum wages or more and work.